Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/joc.3481
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate variability driven by foehn winds in the McMurdo Dry Valleys, Antarctica

Abstract: Warm, dry and gusty foehn winds are frequently experienced in the McMurdo Dry Valleys (MDVs), Antarctica; however, their significance in the region's climate is unknown. Foehn events in the MDVs are caused by topographic modification of southwesterly airflow which is related to the occurrence of synoptic‐scale cyclones in the Amundsen/Ross Sea region. The intra‐ and interannual frequency and intensity of foehn events therefore varies in response to the position and frequency of cyclones in this region that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 78 publications
2
79
0
2
Order By: Relevance
“…A number of different studies have also adopted the same arbitrary thresholds. Speirs et al (2010), Speirs et al (2013), andSteinhoff et al (2014) all identified a föhn wind by an increase of wind speed >5ms -1 , a warming of at least 1 o C and concurrent decrease in relative humidity by 5% per hour. A föhn day was defined as a day that has detected föhn onset and experiences 6 or more continuous hours of föhn conditions with wind speeds >5ms -1 from a consistent wind direction.…”
Section: Föhn Wind Classification Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of different studies have also adopted the same arbitrary thresholds. Speirs et al (2010), Speirs et al (2013), andSteinhoff et al (2014) all identified a föhn wind by an increase of wind speed >5ms -1 , a warming of at least 1 o C and concurrent decrease in relative humidity by 5% per hour. A föhn day was defined as a day that has detected föhn onset and experiences 6 or more continuous hours of föhn conditions with wind speeds >5ms -1 from a consistent wind direction.…”
Section: Föhn Wind Classification Methodsmentioning
confidence: 99%
“…As a result, arbitrary limits are often set to ensure that the daily temperature rises observed are the result of adiabatic warming, instead of diabatic warming with height and/or variable winds (Gaffin, 2007). These thresholds also reduce misclassification and remove weak and brief periods that may not be of interest (Speirs et al 2013). …”
Section: Föhn Wind Classification Methodsmentioning
confidence: 99%
See 3 more Smart Citations